The Influence of Motivation and Work Discipline on Employee Performance at PT. Quarta Medika Indonesia, Tangerang Regency. - Wulandari , Dian; Cahyono, Yoyok; Zakiah, Zakiah (Journal of Industrial Engineering & Management Research, 2025)
This study aims to analyze the influence of motivation and work discipline on employee performance at PT. Quarta Medika Indonesia. The method used is quantitative with a descriptive and associative approach. Data were collected through questionnaires and analyzed using multiple linear regression. The analysis shows that work motivation has a positive and significant impact on employee performance at PT. Quarta Medika Indonesia. Employee performance will increase along with the increase in their motivation level. Work discipline also has a positive and tangible impact on employee work results. Employees who maintain discipline in terms of time, responsibility, and following rules tend to perform better. Companies should improve their motivation programs by providing incentives, recognizing achievements, and providing training and career development. This is important so that employees feel appreciated and motivated at work. Companies need to establish clear and consistent work rules, and show good examples from leaders to build a disciplined work culture. Regular training on the value of discipline should also be held.